The awareness of paying zakat on income: a case study at Sekolah Menengah Kebangsaan Methodist Seremban / Nadiyah Jasmi - Jasmi, Nadiyah (2012)
It is perceived that the awareness on duty to pay Zakat on income by Muslim is still small. The percentage can be improved if they are being educated with the important of it. This situation should not occur because the responsibility to pay Zakat on income must be the most priority as compared to that of an income tax. Thus, this study aims to identify the factors the effect the payment of Zakat on income by Muslim is looking from religious understanding, attitude and ease of payment. This study will use a primary data to get result. Respondents include a teacher and staff who is Muslim at Methodist Seremban. The respondent will be 50 staff and teachers. A total of 50 questionnaires were returned and used to measure the three independent variables which are religious understanding, attitude, and ease of payment towards the awareness of paying Zakat on income. Based on the results obtained, attitude was found to significantly influence to give awareness on paying Zakat on income. It is hoped that the finding of the present study will increase the eligible Muslims awareness to pay Zakat on income and help agency of Zakat institutions to be more efficient and effective in the future.